2011
DOI: 10.15809/irriga.2011v16n3p271
|View full text |Cite
|
Sign up to set email alerts
|

CONSTRUÇÃO E CALIBRAÇÃO DE LISÍMETROS DE PESAGEM PARA DETERMINAÇÃO DA EVAPOTRANSPIRAÇÃO E COEFICIENTE DE CULTIVO EM VIDEIRA DE VINHO cv. SYRAH

Abstract: The most common direct method used to estimate crop evapotranspiration is the lysimetric method. Hence, the objective of this work was to construct, install and evaluate the performance of three weighing lysimeters to estimate the water demand of wine grapes (Vitis viniferal L.) cv. Syrah. The lysimeters, 1.2 m width, 2.0 m long, and 1.0 depth, were Construção e Calibração...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
(14 reference statements)
1
10
0
7
Order By: Relevance
“…The lysimeters were made of metal sheets with dimensions of 1.0 x 1.0 m at the base and 0.7 m of depth, mounted on transverse bars to concentrate all the mass of the set on one load cell located in the center of the system (Carvalho et al, 2007). The calibration of the lysimeters followed the methodology presented by Nascimento et al (2011), obtaining the equations M = 1407.5*(L) -1,077.7 and M = 1372.5*(L) -1,008.5, respectively, for the lysimeters cultivated with the intercropping and in monoculture, in which M is the mass of the set (kg) and L the reading of the load cell (mV).…”
Section: Methodsmentioning
confidence: 99%
“…The lysimeters were made of metal sheets with dimensions of 1.0 x 1.0 m at the base and 0.7 m of depth, mounted on transverse bars to concentrate all the mass of the set on one load cell located in the center of the system (Carvalho et al, 2007). The calibration of the lysimeters followed the methodology presented by Nascimento et al (2011), obtaining the equations M = 1407.5*(L) -1,077.7 and M = 1372.5*(L) -1,008.5, respectively, for the lysimeters cultivated with the intercropping and in monoculture, in which M is the mass of the set (kg) and L the reading of the load cell (mV).…”
Section: Methodsmentioning
confidence: 99%
“…De acordo com Nascimento et al (2011) e Flumignan (2011, a exatidão do equipamento, usualmente, é avaliada por meio do erro padrão (EP). Desta forma, neste estudo, o erro padrão para o sensor variou de 0,602 a 0,643 kg (0,453 a 0,484 mm de ETo) e para o manômetro de 0,424 a 1,050 kg(0,319 a 0,791 mm de ETo).…”
Section: Análise Do Desempenhounclassified
“…The linear regression coefficient (b) varied fro m -66.5319 mm to -67.8924 mm, that is, a difference of 1.3605 mm, wh ich can be attributed to the differences in dead weights of each lysimeter. The mean absolute error varied fro m 0.0272 mm to 0.0382 mm, lo wer than those found by Mariano et al (2015), Nascimento et al (2011), Howell et al (1995, Allen & Fischer (1991) and Faria et al (2006) and similar to Campeche (2002). The mean square error varied fro m 0.0011 mm² to 0.0024 mm², it can be concluded that lysimeters are high ly accurate.…”
Section: Res Ults and Discussionmentioning
confidence: 63%